MD-1 deficiency attenuates dextran sodium sulfate (DSS)-induced colitis through modulating the function of colonic lamina propria dendritic cells. (July 2016) - Pan, Huaqin; Zhang, Guqin; Zhang, Lin; Wang, Wei; Shang, Jian; Wang, Xiaobing; Zhao, Qiu; Li, Jin
Highlights: Elevated MD-1 mRNA is found in the colon of IBD patients and diseased mice. MD-1 −/− mice are protected against DSS-induced colitis characterized by decreased colonic inflammatory gene expression and infiltration of colonic inflammatory cells. MD-1 −/− mice do not alter intestinal permeability after DSS treatment. MD-1 deficiency modulates the function of colonic lamina propria DCs (LPDCs). Abstract: Available evidence suggests that both dysregulated innate and adaptive immune pathways contribute to the aberrant intestinal inflammatory response in patients with inflammatory bowel disease (IBD). Myeloid Differentiation 1 (MD-1), also known as Lymphocyte Antigen 86 (Ly86), a secreted protein interacting with radioprotective 105 (RP105), plays an important role in Toll-like receptor 4 (TLR4) signaling pathway. Previous studies showed that MD-1 may be involved in the (patho) physiological regulation of the innate immune system and inflammation. In this study, we reported for the first time that MD-1 mRNA expression was up-regulated in both human IBD patients and DSS-treated WT mice. We showed that MD-1 −/− mice were less susceptible to the development of colitis than WT controls as demonstrated by significantly reduced weight loss, disease activity index, colon histological scores, cellular infiltration and expression of inflammatory mediators. In addition, mucosal barrier function seemed to be intact in response to the loss of MD-1. Finally, lamina propria dendritic cells (LPDCs) from the colon of MD-1 −/− mice after DSS exposure not only decreased in number but also significantly down-regulated the expression of surface maturation co-stimulatory molecules MHC-II, CD40 and CD86 compared with those from WT mice. Taken together, our results reveal that MD-1 deficiency is of critical importance in down-regulating induction and progression of DSS colitis, thereby suggesting that MD-1 might be a target for future interventional therapies of IBD.